1992
DOI: 10.1007/bf01270575
|View full text |Cite
|
Sign up to set email alerts
|

Annexins in cardiac tissue: cellular localization and effect on phospholipase activity

Abstract: Stimulation of cardiac phospholipid metabolism has diverse biological effects, ranging from subtle changes in cellular function to severe cellular damage. Accordingly, knowledge of the factors governing the activity of cardiac phospholipases is of great biological importance. A possible role of annexins, intracellular proteins that bind to membranes in a calcium dependent manner, as modulators of phospholipase activity has been proposed. In this study we investigated the cell type specific distribution of Anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Taken together, our results indicated that annexin V was present in sarcolemma, and intercalated discs, and in the T-tubules connected to the terminal cisternae of sarcoplasmic reticulum -the complex in which the excitation-contraction coupling took place. Therefore, labeling of annexin V in human heart was similar to that of other species (Doubell et al, 1993;Jans et al, 1995;Luckcuck et al, 1997;Trouvé et al, 1999;Van Bilsen et al, 1992;Wang et al, 1995). Interestingly, immunofluorescence of annexin V in failing hearts (Fig.…”
Section: Annexins In Failing Human Heartmentioning
confidence: 79%
See 2 more Smart Citations
“…Taken together, our results indicated that annexin V was present in sarcolemma, and intercalated discs, and in the T-tubules connected to the terminal cisternae of sarcoplasmic reticulum -the complex in which the excitation-contraction coupling took place. Therefore, labeling of annexin V in human heart was similar to that of other species (Doubell et al, 1993;Jans et al, 1995;Luckcuck et al, 1997;Trouvé et al, 1999;Van Bilsen et al, 1992;Wang et al, 1995). Interestingly, immunofluorescence of annexin V in failing hearts (Fig.…”
Section: Annexins In Failing Human Heartmentioning
confidence: 79%
“…Annexins V and VI are the major annexins in porcine (Pula et al, 1990), bovine (Iida et al, 1992;Wang et al, 1993;Zeng et al, 1993), rat (Doubell et al, 1993;Jans et al, 1995;Wang et al, 1995), and guinea pig (Trouvé et al, 1999) myocardium. Annexin V is able to form voltage-gated Ca 2ϩ channels (Pollard et al, 1992) and to modulate activity of protein kinase C and phospholipase A 2 Mira et al, 1998;Van Bilsen et al, 1992). In myocardium, the localization of annexin V is not clearly established: the presence of annexin V was first reported in endothelium and fibroblasts (Van Bilsen et al, 1992), then in myocytes in which it has been detected either in cytosol (Jans et al, 1995), in membranes (Luckcuck et al, 1997;Trouvé et al, 1999), or associated with Z-lines (Trouvé et al, 1999;Wang et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another biological function described for Annexin V is an anti phospholipase A2 activity. This activity is based on the same principle as the anticoagulant function of Annexin V, namely shielding off of the negatively charged phospholipids, the substrate for phospholipase A2 (13,57,58,60,61,67,79,88,89). Based on this activity, it has been postulated that Annexins participate in inflammatory processes.…”
Section: Other Functions Of Annexin Vmentioning
confidence: 99%